2016
DOI: 10.1042/bcj20160328
|View full text |Cite
|
Sign up to set email alerts
|

Identification of adducin-binding residues on the cytoplasmic domain of erythrocyte membrane protein, band 3

Abstract: Two major complexes form structural bridges that connect the erythrocyte membrane to its underlying spectrin-based cytoskeleton. Although the band 3-ankyrin bridge may account for most of the membrane-to-cytoskeleton interactions, the linkage between the cytoplasmic domain of band 3 (cdb3) and adducin has also been shown to be critical to membrane integrity. In this paper, we demonstrate that adducin, a major component of the spectrin-actin junctional complex, binds primarily to residues 246 through 264 of cdb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…51,52 Although all of these functions contribute critically to RBC biology, its role in linking the cytoskeleton to the membrane may be most critical, because rupture of either the band 3-ankyrin or the band 3-adducin bridge to the spectrin-based membrane skeleton leads to membrane destabilization and fragmentation. [53][54][55] Interestingly, Syk inhibitors do not apparently play a role in the assembling of parasite proteins that ultimately lead to the formation of knobs in the host cell membrane. 56 Previous work has shown that phosphorylation of tyrosines 8 and 21 in the cytoplasmic domain of band 3 in fact causes dissociation of ankyrin from band 3, resulting in rupture of the major bridge linking band 3 to the cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 Although all of these functions contribute critically to RBC biology, its role in linking the cytoskeleton to the membrane may be most critical, because rupture of either the band 3-ankyrin or the band 3-adducin bridge to the spectrin-based membrane skeleton leads to membrane destabilization and fragmentation. [53][54][55] Interestingly, Syk inhibitors do not apparently play a role in the assembling of parasite proteins that ultimately lead to the formation of knobs in the host cell membrane. 56 Previous work has shown that phosphorylation of tyrosines 8 and 21 in the cytoplasmic domain of band 3 in fact causes dissociation of ankyrin from band 3, resulting in rupture of the major bridge linking band 3 to the cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…In the third system containing anionic DSPS, additional sodium ions were added to neutralize the system. Band 3 (PDB: 4YZF) consists of 911 residues which are divided into two domains: the N-terminal cytoplasmic domain (cdAE1, residues 1–360) and the C-terminal membrane domain (mdAE1, residues 361–911). The cdAE1 is associated with the cytoskeleton of erythrocytes, while the mdAE1, which consists of 14 transmembrane (TM) helices and 6 hydrophilic helices, is mainly responsible for the anion exchange function. In this work, we focus on the interactions between mdAE1 and lipid nanodomains. The structure of mdAE1 as well as a full lipid bilayer with mdAE1 simulated in this work are shown in Figure b and c.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Peripheral proteins include band 4.2 (331,337) and the glycolytic enzyme complex (295). 3) Adducin complex (338,339), at the spectrin-actin junction. The adducin complex is larger than the ankyrin complex and includes band 4.1, dematin, stomatin, and many other integral and peripheral proteins (7,333,340), including the glucose transporter GLUT1 (341).…”
Section: Summary Of Band 3 Complexesmentioning
confidence: 99%